Legal Analysis of Protocol-Holding Notaries Liability for Disputed Notarial Protocols - I Gst Ayu Kiara Saraswati Putri Swastika; Dita Perwitasari; Reva Febrizea Marcha (Universitas Negeri Surabaya, 2026)
This study examines the boundaries of legal responsibility of a notary who holds another notary's protocol when that protocol becomes the object of a court dispute, an issue not explicitly regulated under Indonesia's Notary Law (UUJN-P). Using normative legal research with a statutory and conceptual approach, this study analyzes Articles 62–65 of UUJN-P through grammatical, systematic, and teleological interpretation, supported by three court cases in which protocol-holding notaries were joined as co-defendants despite having no role in drafting the disputed deeds. The results show that UUJN-P only regulates the administrative mechanism of protocol transfer and safekeeping, without defining the scope of liability once a stored deed is disputed. Interpretive analysis indicates that the protocol-holding notary's responsibility is limited to administrative-procedural duties safekeeping, maintaining, and issuing copies of deeds while substantive responsibility for the deed's content remains with the notary who originally drafted it. Civil liability may only arise if negligence or unlawful conduct in managing the protocol is proven under Article 1365 of the Civil Code, and administrative sanctions require proven breach of custodial duty under Article 85 UUJN-P. Protocol-holding notaries may pursue preventive measures (formal handover reports) and repressive measures (raising exceptions in court, seeking institutional protection from the Notary Honorary Council and the Indonesian Notary Association). This study recommends that lawmakers amend UUJN-P to explicitly define the limits of a protocol-holding notary's liability.